2021 FDA TIDES (Peptides and Oligonucleotides) Harvest - Danah Al Shaer; Othman Al Musaimi; Fernando Albericio; Beatriz G. de la Torre (MDPI AG, 2022)
From the medical, pharmaceutical, and social perspectives, 2021 has been a year dominated by the COVID-19 pandemic. However, despite this global health crisis, the pharmaceutical industry has continued its endeavors, and 2021 could be considered an excellent year in terms of the drugs accepted by the US Food and Drug Administration (FDA). Thus, during this year, the FDA has approved 50 novel drugs, of which 36 are new chemical entities and 14 biologics. It has also authorized 10 TIDES (8 peptides, 2 oligonucleotides), in addition to 2 antibody-drug conjugates (ADCs) whose structures contain peptides. Thus, TIDES have accounted for about 24% of the approvals in the various drug categories. Importantly, this percentage has surpassed the figure in 2020 (10%), thus reflecting the remarkable success of TIDES. In this review, the approved TIDE-based drugs are analyzed on the basis of their chemical structure, medical target, mode of action, administration route, and adverse effects.